PENGARUH BRAND CREDIBILITY TERHADAP WORD OF MOUTH MELALUI CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY - Karisha Alifputri; Rudy Pramono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This research aims to examine the positive effect of brand credibility on word of mouththrough customer satisfaction and customer loyalty at Tokopedia. The internet has hada dramatic effect in influencing business behavior which is now utilized to facilitate therefinement and processing of business transactions known as e-commerce. Tokopedia isan e- commerce made by the nation's children who has become the number 1 unicorncompany in Indonesia. However, due to the intense e-commerce competition inIndonesia, Tokopedia has shifted its position. There was a problem with Tokopedia'ssecurity where as many as 91 million Tokopedia user data was leaked and sold on thedark web. This prompts research upon Tokopedia’s brand credibility on word of mouththrough customer satisfactionand customer. The sampling technique in this study uses a non-probability samplingtechnique, namely convenience sampling where the respondents are Tokopedia customers in Jabodetabek. The sample in this studyamounted to 154 respondents with the data collection method in the form of aquestionnaire. The data were processed using validity, reliability, and statisticalanalysis. Data processing using Partial Least Square – Structural Equation Modeling(PLS-SEM) was processed using SmartPLS software. The results showed that the brandcredibility variable had a positive influence, either directly or indirectly, on word ofmouth mediated by customer satisfaction and customer loyalty